SEBERAPA EFEKTIF INTERACTIVE FLAT PANEL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN? TINJAUAN LITERATUR SISTEMATIS : [HOW EFFECTIVE ARE INTERACTIVE FLAT PANELS IN IMPROVING THE QUALITY OF LEARNING? A SYSTEMATIC LITERATURE REVIEW] - Rizal Dhiky Hermawan; Anik Widiastuti (Polyglot, 2026)
The digital transformation of education is driving the use of Interactive Flat Panels (IFPs) as interactive learning tools capable of improving the quality of learning. Various studies have demonstrated the benefits of IFPs; however, existing findings remain limited and do not yet provide a comprehensive picture of the trends, effectiveness, and factors supporting their implementation. This study aims to analyze trends and the effectiveness of IFP utilization through a Systematic Literature Review (SLR). The method employed is a qualitative approach guided by the PRISMA guidelines. Data were obtained from Google Scholar, SINTA, and Scopus using keywords related to IFP. Of the 85 articles identified, 15 duplicates were removed, 40 were eliminated during the screening phase, and 20 were excluded during the eligibility phase, resulting in 10 articles for analysis. The results indicate that IFP effectively improves student learning outcomes, conceptual understanding, motivation, engagement, and collaboration. The effectiveness of IFP is influenced by teacher competence, digital literacy, learning strategies, and school management support. Teacher training and strengthening the implementation of technology in schools are recommended. In conclusion, IFP effectively enhances learning in cognitive, affective, and social aspects and has the potential to support interactive, innovative, and sustainable education at all levels. Abstrak Bahasa Indonesia Penelitian ini bertujuan untuk menganalisis tren dan efektivitas pemanfaatan Interactive Flat Panel (IFP) dalam meningkatkan kualitas pembelajaran melalui pendekatan Systematic Literature Review (SLR). Metode yang digunakan adalah kualitatif dengan prosedur SLR melalui tahapan identifikasi, penyaringan, uji kelayakan, dan inklusi berdasarkan alur PRISMA. Data diperoleh dari Google Scholar, Sinta, dan Scopus. Dari 85 artikel yang ditemukan, diseleksi hingga diperoleh 10 artikel yang memenuhi kriteria untuk dianalisis. Hasil penelitian menunjukkan bahwa IFP efektif dalam meningkatkan kualitas pembelajaran. Berdasarkan sintesis tabel, IFP unggul dalam meningkatkan hasil belajar kognitif melalui visualisasi materi yang konkret, memperkuat pemahaman konsep, serta mendukung pembelajaran interaktif dan inovatif. Pada aspek afektif, IFP meningkatkan motivasi belajar, motivasi intrinsik, serta keterlibatan dan keaktifan siswa. Integrasi dengan model seperti gamifikasi dan Project-Based Learning juga meningkatkan kolaborasi siswa. Namun, efektivitas IFP dipengaruhi oleh kompetensi dan literasi digital guru serta manajemen sekolah. Oleh karena itu, direkomendasikan pelatihan guru dan penguatan implementasi berbasis teknologi. Kesimpulannya, IFP efektif meningkatkan kualitas pembelajaran secara komprehensif dengan dukungan sistem yang memadai.